Effectiveness of Bacillus subtilis in enhancing regulatory hormones and inhibiting the main fungus causing root rot in date palm offshoots (Phoenix dactylifera L.) - Jassim, Naji Salim; Khassaf, Wafa Hasach; Jaafer, Mahmood Oda (Basrah Journal Of Date Palm Research, 2025)
Root rot disease in date palm nurseries and new plantations has raised serious concern among farmers in Basrah Governorate, Iraq. Date palm offshoots (Phoenix dactylifera L.) are particularly vulnerable to this disease. Pathogenicity tests identified Fusarium. oxysporum, Fusarium. proliferatum S1, Fusarium. proliferatum S2, and Fusarium fujikuroi were the causative agents of the root rot disease in date palm offshoots. Among them, F. oxysporum was the most virulent,, causing a severity index of 84.2% of root rot and a recorded severity level of 4 (root discoloration of up to 76% or more than one wilted leaf). In contrast, R. solani was the least pathogenic, with a disease severity percentage of 16.2%. In a dual-culture test on a PDA medium, Bacillus. subtilis exhibited antagonistic effects on the growth of F. oxysporum, leading to an 86% inhibition of mycelial growth development (1.2 cm diameter of colony growth fungus). The control(fungus alone) showed typical fungal growth (9 cm diameter for colony growth). Results from the greenhouse experiment indicated that plantlets treated with B. subtilis in conjunction with F. oxysporum showed increased production of indole acetic acid (IAA) and indole butyric acid (IBA) while the level of abscisic acid (ABA) was decreased compared to plantlets treated only with F. oxysporum.